Expressional and prognostic value of HPCAL1 in cholangiocarcinoma via integrated bioinformatics analyses and experiments. (29th May 2022) - Ma, Mingjian; Zeng, Guangyan; Li, Jinhui; Liang, Jiahua; Huang, Li; Chen, Jiancong; Lai, Jiaming
Abstract: Background: Hippocalcin‐like 1 (HPCAL1) is involved in the development of several cancer types. However, our understanding of the HPCAL1 activity in cholangiocarcinoma (CCA) remains limited. Methods: Two microarray datasets were used to screen for differentially expressed genes (DEGs) involved in the development of CCA. The Cancer Genome Atlas (TCGA)/Gene Expression Omnibus (GEO) database was integrated to determine the prognostic significance of DEGs in CCA. The association between clinical characteristics and HPCAL1 expression levels was initially explored to assess the clinical profile of CCA. The prognostic value of HPCAL1 overexpression in the validation cohort was analyzed, followed by Gene Ontology (GO) term analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis of HPCAL1. Results: Three upregulated genes and 10 downregulated genes were detected from two microarray‐based screenings. High expression of HPCAL1 as a poor prognostic factor of CCA was validated using TCGA/GEO integrated database and our database. Univariate and multivariate analyses along with Kaplan–Meier survival analysis showed that high HPCAL1 expression was an independent factor affecting the overall survival and relapse‐free survival in patients with CCA. The high expression of HPCAL1 was significantly associated with cancer antigen 125 (CA‐125) levels, number of tumors, lymph node invasion, and TNM stage. Analysis of the enriched GO terms and KEGG pathways revealed that the high expression of HPCAL1 was involved in the critical biological processes and molecular pathways, including modulation by a host of symbiont processes, the clathrin coat, actinin binding, and Rap1 signaling pathways. Conclusion: HPCAL1 was enriched in CCA in our study and has the potential to be applied in the identification of patients with CCA with an unfavorable prognosis. Abstract : (A) IHC staining for HPCAL1 (B) Multivariate Cox analysis of clinicopathological variables and OS/RFS (C) Overall survival and relapse‐free survival in CCA patients with different levels of HPCAL1.